2019
DOI: 10.3390/rs11030296
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Signal from Diverse Optical Sensors for Monitoring Alpine Grassland Dynamics

Abstract: Grasslands cover up to 40% of the mountain areas globally and 23% of the European Alps and affect numerous key ecological processes. An increasing number of optical sensors offer a great opportunity to monitor and address dynamic changes in the growth and status of grassland vegetation due to climatic and anthropogenic influences. Vegetation indices (VI) calculated from optical sensor data are a powerful tool in analyzing vegetation dynamics. However, different sensors have their own characteristics, advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 59 publications
0
25
0
1
Order By: Relevance
“…In this paper, we show that the derived NDVI values from UAVs and PlanetScope CubeSat imagery across treatments are largely consistent with important differences, particularly in their sensitivity to subtle changes to water content (control and water). Studies have shown that vegetation indices, such as NDVI, can be significantly affected by differences in spectral bandwidth [61,69]. The spectral range of the red band has been found to be of importance to NDVI.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we show that the derived NDVI values from UAVs and PlanetScope CubeSat imagery across treatments are largely consistent with important differences, particularly in their sensitivity to subtle changes to water content (control and water). Studies have shown that vegetation indices, such as NDVI, can be significantly affected by differences in spectral bandwidth [61,69]. The spectral range of the red band has been found to be of importance to NDVI.…”
Section: Discussionmentioning
confidence: 99%
“…Some variability occurred between time points in all bands and NDVI; likely a result of the UAV and Tec5 spectrometer obtaining measurements at different spatial resolutions [38] and datasets not being collected on the same date. Rossi et al [44] demonstrated the impact of non-concurrent data collection when comparing different reflectance from different sensors, with a single day lag negatively impacting on correlation results. Variability in accuracy also occurred between bands, particularly for visible versus NIR, which was observed consistently over time.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the aforementioned RTM limitations and the fact that the new satellite missions are providing several bands across the RE and the NIR shoulder regions, further research is expected on the ability of SVIs based on such regions to retrieve LAI and on the spectral response mechanisms at the canopy level in different vegetation types [29], which are not yet fully explored [30,31]. RE SVIs (which make use of the RE spectral region) include the RE-based normalized difference vegetation index (RENDVI [32]) and the chlorophyll index (CIre [33]).…”
Section: Red-edge and Nir-shoulder Svismentioning
confidence: 99%